2022
DOI: 10.1088/1361-6587/ac5bb6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the electromagnetic topology during the ohmic breakdown in tokamaks considering self-generated electric fields

Abstract: The physical mechanisms of the ohmic breakdown in a tokamak have been understood based on the classical Townsend avalanche theory. However, a new systematic theory [Yoo, Nat. Commun. \textbf{9} 3523 (2018)] recently demonstrated that electron avalanches during the ohmic breakdown are completely different from the Townsend avalanche due to strong self-generated electric fields. In this study, we elucidate the multi-dimensional effects of the self-generated electric field on plasma dynamics during the ohmic brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…The analyses of the breakdown time in NSTX [52] and KSTAR [87] have shown that the Townsend model of equation is insufficient for reproducing the timescale of experimental I p and n e rises, and a mechanism for shielding applied electric fields is required. Numerical studies using PIC simulations [87][88][89][90] have proposed that when ionisation proceeds, self-consistent electric fields formed by the charge separation of electrons and ions shield the applied electric field and retard the breakdown. A simple expression for estimating the self-consistent toroidal electric field that shields the external drive is [87]:…”
Section: Appendix a Townsend Avalanche Model In The Index-s Codementioning
confidence: 99%
“…The analyses of the breakdown time in NSTX [52] and KSTAR [87] have shown that the Townsend model of equation is insufficient for reproducing the timescale of experimental I p and n e rises, and a mechanism for shielding applied electric fields is required. Numerical studies using PIC simulations [87][88][89][90] have proposed that when ionisation proceeds, self-consistent electric fields formed by the charge separation of electrons and ions shield the applied electric field and retard the breakdown. A simple expression for estimating the self-consistent toroidal electric field that shields the external drive is [87]:…”
Section: Appendix a Townsend Avalanche Model In The Index-s Codementioning
confidence: 99%